A cross-cultural analysis of the relations of physical and relational aggression with peer victimization. (January 2018) - Bass, Ellyn Charlotte; Saldarriaga, Lina; Cunha, Josafa; Chen, Bin-Bin; Santo, Jonathan Bruce; Bukowski, William M.
To better address the many consequences of peer victimization, research must identify not only aspects of individuals that put them at risk for victimization, such as aggression, but also aspects of the context that influence the extent of that risk. To this end, this study examined the contextual influences of gender, same-sex peer group norms of physical and relational aggression, and nationality on the associations of physical and relational aggression with peer victimization in early adolescents from Canada, China, Brazil, and Colombia ( N = 865; Mage = 11.01, SD = 1.24; 55% boys). Structural equation modeling was used to test for measurement invariance of the latent constructs. Multilevel modeling revealed that both forms of aggression were positive predictors of peer victimization, but physical aggression was a stronger predictor for girls than boys. Cross-national differences emerged in levels of peer victimization, such that levels were highest in Brazil and lowest in Colombia. Cross-national differences were also evidenced in the relationship between relational aggression and victimization: the relationship was positive in China, Brazil, and Canada (listed in descending order of magnitude), but negative in Colombia. Above and beyond the cross-national differences, physical aggression was a stronger predictor of victimization in peer groups low in physical aggression, and relational aggression was a stronger predictor in peer groups low in relational aggression. Ultimately, this research is intended to contribute to a better theoretical understanding of risk factors for peer victimization and the development of more effective and culturally-appropriate prevention and intervention efforts.